PENGARUH KECERDASAN BUATAN DALAM STRATEGI PEMASARAN DIGITAL - Purnama, Purnama; Susanti, Febri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Artificial Intelligence (AI) has become a major element in digital marketing strategies, influencing the way companies understand, reach and interact with consumers. This research aims to explore how AI is applied in digital marketing strategies from a qualitative perspective, focusing on the experiences and perceptions of digital marketing practitioners. This research adopts a qualitative approach with an in-depth interview method to explore digital marketing practitioners' understanding of the use of AI in their strategy. The interviews were conducted in a semi-structured manner to enable further exploration of their experiences, perceptions, and challenges. Through in-depth interviews with practitioners in various sectors, this research reveals the challenges, opportunities, and impact of AI on digital marketing strategies in various industries. The findings of this research are expected to provide a more comprehensive insight into the role of AI and its implications for innovation in digital marketing